Estrategias didácticas para la enseñanza de inglés como lengua extranjera (EFL) dirigidas a estudiantes con trastorno por déficit de atención e hiperactividad (TDAH) - De la Cruz, Gabriela; Ullauri Moreno, Magdalena Inés; Freire, Jenny (Colombian Applied Linguistics Journal, 2020)
The acquisition of a language is a complex process and it is even more for students with ADHD, this work proposes the detection of methodological strategies to teach English as a foreign language (EFL) to a 14-year-old boy who has a disorder of attention deficit hyperactivity disorder (ADHD). The analysis of the topic is important since there is very little literature that addresses it using a case study. The research is qualitative and heuristic, because it aims to discover an appropriate methodology for teaching English to a young person with ADHD. The English teacher and the psychologist of the educational institution were interviewed to obtain a deep understanding of the student’s context. Subsequently, various English teaching-learning methodologies were applied during 6 sessions. The observation sheets show that there are changes in the student’s behavior after the intervention, such as: less interruption in class, greater self-control and less sudden movements. The results allow us to conclude that the application of methodological strategies for teaching English that promote creativity and proactivity are beneficial for a student with ADHD.